2017
DOI: 10.1016/j.icarus.2017.02.025
|View full text |Cite
|
Sign up to set email alerts
|

An orbital meteoroid stream survey using the Southern Argentina Agile MEteor Radar (SAAMER) based on a wavelet approach

Abstract: Over a million individually measured meteoroid orbits were collected with the Southern Argentina Agile MEteor Radar (SAAMER) between 2012-2015. This provides a robust statistical database to perform an initial orbital survey of meteor showers in the Southern Hemisphere via the application of a 3D wavelet transform. The method results in a composite year from all 4 years of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…With the advent of new ground‐based and space‐borne observations of the Moon there exists new interest in understanding the differences between the lunar and terrestrial meteoroid environments. Like for the case of Mercury (Pokorný et al, , ), modeling the meteoroid flux on the Moon is critical for understanding the importance of impact vaporization as a source for the lunar exosphere (Bruno et al, ; Cremonese et al, ; Morgan et al, ; Morgan & Killen, ; Sarantos et al, ), as meteoroids in the size range of 5–200 μm are considered relevant to the daily resupply of the lunar atmosphere. The importance of impacts for the exosphere was demonstrated by the brightening of its sodium and potassium component during meteor showers (Barbieri et al, ; Colaprete et al, ; Smith et al, ; Szalay et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of new ground‐based and space‐borne observations of the Moon there exists new interest in understanding the differences between the lunar and terrestrial meteoroid environments. Like for the case of Mercury (Pokorný et al, , ), modeling the meteoroid flux on the Moon is critical for understanding the importance of impact vaporization as a source for the lunar exosphere (Bruno et al, ; Cremonese et al, ; Morgan et al, ; Morgan & Killen, ; Sarantos et al, ), as meteoroids in the size range of 5–200 μm are considered relevant to the daily resupply of the lunar atmosphere. The importance of impacts for the exosphere was demonstrated by the brightening of its sodium and potassium component during meteor showers (Barbieri et al, ; Colaprete et al, ; Smith et al, ; Szalay et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…More observations , including multiyears, seasons, and sky coverage, enable the identification of expected and/or unexpected outbursts. For example, Jenniskens et al (2016a) reported a Volantid shower outburst, a high southern ecliptic latitude shower that showed unexpected high activity only during 2015 New Year's Eve according to both optical and radar measurements (Younger et al 2016;Pokorný et al 2017). More recently, comparisons between radar and optical observations have shown specific showers to have differences in the evolutionary stages of their different mass ranges (Jeniskens et al 2018;Bruzzone et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike sporadics, meteoroids within streams move in approximately parallel paths and at nearly the same speed. The Earth intersects numerous streams in its annual trek around the sun, resulting in periods of increased flux, or showers, of meteoroids at the top of the atmosphere (Brown et al 2010;Pokorný et al 2017a;. Although the SMC is responsible for providing a constant source of impactors to create and maintain exospheres on airless bodies, events produced by meteoroid streams offer a unique opportunity to study the physical processes involved in this phenomena with a much more constrained input (e.g., velocity distribution, directionality, temporal variability, etc).…”
Section: Effects Due To Meteor Showersmentioning
confidence: 99%